Decolonizing Forest: The Myth of Panjurli and Guliga in Kantara (2022) - Anandita Saraswat; Aratrika Das (Religions)
Colonial ideologies reduce nature to a repository of extractable resources and portray the Indigenous communities’ religious understanding of nature as primitive and unscientific. Decolonization foregrounds the silenced Indigenous epistemes that critique exceptional human paradigms of colonial modernity. This paper examines how traditional religious rituals function as a method of decolonization and discusses their exclusion from Western academia. It focuses on Kantara’s cinematic representation of the Indigenous ritual of Bhoota Kola and the worship of forest deities, Panjurli and Guliga, in the coastal areas of southern Karnataka and Kerala. These rituals emphasize the agency of the environment, where the forest, humans, and deities are porous and permeable. This non-anthropocentric understanding of humans questions the dominance of the secular narratives of posthuman theories in Western academia. Rituals foster ecological behaviours and highlight multispecies relationality, providing alternatives for sustainable futures. In emphasizing Indigenous religious practices, the paper undisciplines the Eurocentric study of religion and questions the disciplinary boundaries between scientific thought and Indigenous knowledge. Thus, this paper argues for the inclusion of regional cinemas from the Global South in Western academia to foreground Indigenous epistemes that undiscipline the study of religion and science.